Use of extruded soy flour in milk replacers for calves - D.P. Dawson; J.L. Morrill; P.G. Reddy; Keith C. Behnke (Kansas Agricultural Experiment Station Research Reports, 1987)
Oil-extracted, desolveritized soy flour without additional heat treatment was used to prepare protein supplements for calf milk replacers by extrusion processing. Various combinations of temperature, moisture, calcium concentration, sulfur, and acid were used to prepare 32 different products. These products were tested for trypsin inhibitor and antigenic activity and the most promising one was chosen for further testing. This product alone or with supplementary amino acids or amino acids and citric acid was used to provide 70% of the protein in experimental milk replacers. These replacers were compared to an all-milk replacer, using growth and metabolic responses of young Holstein bull calves. The extruded soy protein was inferior to milk protein but calf performance was sufficient to indicate a potential for this kind of product in areas where milk products are prohibitively expensive. Amino acid supplementation of this soy product was not beneficial. Acidification had some benefit in the young (old) calf, but was not beneficial later.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Soy flour; Milk replacer; Amino acid; Trypsin